2014
DOI: 10.1124/dmd.114.058446
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Centrifugation: Accounting for Transporter Protein Losses in Quantitative Targeted Absolute Proteomics

Abstract: In drug development, considerable efforts are made to extrapolate from in vitro and preclinical findings to predict human drug disposition by using in vitro-in vivo extrapolation (IVIVE) approaches. Use of IVIVE strategies linked with physiologically based pharmacokinetic (PBPK) modeling is widespread, and regulatory agencies are accepting and occasionally requesting model analysis to support licensing submissions. Recently, there has been a drive to improve PBPK models by characterizing the absolute abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 34 publications
2
47
1
Order By: Relevance
“…Considering this information gap, we have recently published a study that characterized, for the first time, gene expression and protein abundance of clinically important transporters along the entire length of human intestine using paired tissues from organ donors (thereby avoiding the intersubject variability bias) . However, a considerable limitation of that analysis was protein determination in the isolated crude membrane fraction, which carried the risk of loss of protein and/or overestimation or underestimation of certain transporters compared to whole‐tissue lysates, as performed in this study, and has also been demonstrated in a recent comparative study on proteomics of absorption, distribution, metabolism, and excretion proteins . Therefore, we used the Filter‐Aided Sample Preparation (FASP) method to overcome this limitation in this study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Considering this information gap, we have recently published a study that characterized, for the first time, gene expression and protein abundance of clinically important transporters along the entire length of human intestine using paired tissues from organ donors (thereby avoiding the intersubject variability bias) . However, a considerable limitation of that analysis was protein determination in the isolated crude membrane fraction, which carried the risk of loss of protein and/or overestimation or underestimation of certain transporters compared to whole‐tissue lysates, as performed in this study, and has also been demonstrated in a recent comparative study on proteomics of absorption, distribution, metabolism, and excretion proteins . Therefore, we used the Filter‐Aided Sample Preparation (FASP) method to overcome this limitation in this study.…”
Section: Discussionmentioning
confidence: 86%
“…The resulting protein abundance data along with information on the yield of enriched membrane protein from a certain amount of hepatocytes or liver tissue could be translated into transporter abundance in hepatocytes or in the liver . However, there is a potential bias in these conversions/calculations . Therefore, the advantage of the current study is the availability of data from liver tissue lysates that could be directly used without further conversion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher abundance should be expected, at least theoretically, in the plasma membrane fraction, which is anticipated to be more transporterenriched and functionally pertinent. Arguably, losses attributable to plasma membrane preparation methods could be responsible for this contradiction, as highlighted recently (Harwood et al, 2014). Plasma membrane may contain only a fraction of the total expressed transporter attributable to potential internalization reported for several (Bow et al, 2008;Kock et al, 2010;Choi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To address whether there are laboratory-specific differences in generating system parameters for undertaking transporter-mediated IVIVE-PBPK, a multicenter study evaluating the consistency and comparability of the preparation steps and analytic outcome has been advocated (Harwood et al, 2014). However, to our knowledge, studies comparing the quantification of absolute transporter-protein abundances and the subsequent generation of REFs between laboratories for the same samples have not been reported in the literature yet.…”
Section: Introductionmentioning
confidence: 96%